EFFECTIVENESS OF EARLY POSTOPERATIVE EXERCISE PROGRAM IN POST HIP ARTHROPLASTY PATIENTS - Arif Pristianto; Prihantoro Larasati Mustiko; Taufik Eko Susilo (P3M Universitas 'Aisyiyah Surakarta, 2023)
Background: Patients after undergoing arthroplasty surgery will experience several changes in carrying out functional activities and daily routines. This is due to altered joint and muscle function due to decreased strength and limited range of motion after arthroplasty surgery. Post-hip arthroplasty conditions require comprehensive treatment so as not to cause impairment/disability that will interfere with function and gait. How effective is the early postoperative exercise program in preventing further decline in ability and speeding recovery? Methods: This exercise program is given since the patient has finished surgery and is gradually progressing to standing and walking exercises. This research was conducted on patients in the inpatient room of RS Ortopedi Prof. Dr. R. Soeharso Surakarta. Assessment and evaluation of post-hip arthroplasty results using the Harris Hip Score functional index before and after being given an exercise program. Results: The statistical test showed that the data was not normally distributed (p<0.05) and the results of the influence test using the Wilcoxon Test showed that there was an effect of early postoperative exercise on reducing pain (p=0.005) and increasing the Harris Hip Score (HHS) index. The result of the action is that there is an increase in functional ability in post-hip arthroplasty patients. Conclusion: Based on this study, it can be concluded that the program of giving exercise therapy as early as possible in post-hip arthroplasty patients can accelerate recovery and improve functional ability.